Calcified fibrous nodules in masseter muscle - A case report and possible etiologies - Barros, Renata Cunha; Gonçalves, Gabriela Mendes; Moreira, David; Setubal, Miguel Andrade; Ramos, Eduardo Gonçalves; Medrado, Alena Ribeiro Alves Peixoto (Journal of Oral Diagnosis, 2016)
Fibro-calcified nodules represent a rare group of lesions that are composed of fibrous connective tissue with calcified areas. The etiology of fibro-calcified nodules may be related to secondary changes that are caused by trauma, infectious and autoimmune diseases, or calcified thrombi. The purpose of this paper is to report the presence of a lesion of a fibro-calcified nature in the masseter muscle and its possible etiologies. The patient, a 35-year-old melanoderm female, presented with a nodule in the left masseter region with 12 months of pro- gression. Considering the accessibility of the lesion, an excisional biopsy was performed. A histopathological examination revealed residual fibro-calcified nodules with central foci of coagulation necrosis surrounded by fatty tissue and striated skeletal muscle fibers. The test for acid-alcohol-resistant bacillus (BAAR) was negative. Two years after the surgical procedure, there were no signs of lesion recurrence. Thus, the results of histochemical staining ratified the fibro-calcified aspect of the lesion, which suggested dystrophic calcification.